2016
DOI: 10.3389/fpsyg.2016.01940
|View full text |Cite
|
Sign up to set email alerts
|

Time-Series Analysis of Embodied Interaction: Movement Variability and Complexity Matching As Dyadic Properties

Abstract: There is a growing consensus that a fuller understanding of social cognition depends on more systematic studies of real-time social interaction. Such studies require methods that can deal with the complex dynamics taking place at multiple interdependent temporal and spatial scales, spanning sub-personal, personal, and dyadic levels of analysis. We demonstrate the value of adopting an extended multi-scale approach by re-analyzing movement time-series generated in a study of embodied dyadic interaction in a mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 46 publications
3
29
0
Order By: Relevance
“…This dyadic nature of the interaction was further supported by a re-analysis of the sensorimotor time series by Zapata-Fonseca et al (2016) . They revealed that the clustering statistics (Allan factor) of discrete movement events was characterized by fractal scaling, which highlights that the social interaction process operates in a distributed fashion across multiple timescales.…”
Section: Introductionmentioning
confidence: 63%
“…This dyadic nature of the interaction was further supported by a re-analysis of the sensorimotor time series by Zapata-Fonseca et al (2016) . They revealed that the clustering statistics (Allan factor) of discrete movement events was characterized by fractal scaling, which highlights that the social interaction process operates in a distributed fashion across multiple timescales.…”
Section: Introductionmentioning
confidence: 63%
“…Conceptual and experimental practices should be developed hand-inhand with methods of analysis (e.g. Bahrami et al 2010;Konvalinka and Roepstorff 2012;Schilbach et al 2013;Abney et al 2014;Dumas et al 2014;Froese et al 2015;Friston and Frith 2015;Zapata-Fonseca et al 2016;Fusaroli and Tylén 2016;Sevgi et al 2016;Bolis and Schilbach 2017a). Here, we suggest a shift from an exclusive focus on the (Bayesian) brain in isolation, toward a multilevel understanding of intersubjectivity and psychopathology.…”
Section: Two-person Psychophysiology and Multi-level Accounts Of Intersmentioning
confidence: 97%
“…It is important to stress that there exists further research directed toward the foundation of social learning [9][10][11][12] that is even more closely connected to the ambitious challenge made by Ashby. In fact, this research aims at evaluating the transfer of information from the brain of one player to that of another, by way of the interaction the two players established through their avatars [10].…”
Section: Introductionmentioning
confidence: 99%